2019
DOI: 10.7771/1541-5015.1752
|View full text |Cite
|
Sign up to set email alerts
|

Examining Science Learning and Attitude by At-Risk Students After They Used a Multimedia-Enriched Problem-Based Learning Environment

Abstract: Most of the previous problem-based learning (PBL) studies have been conducted with gifted or regular education students and have shown successes. However, little research on PBL exists for disadvantaged middle school students, especially students who are considered to be at risk of failing academically. In this study, we examined the use of a multimedia-enriched PBL science environment by at-risk middle school students. The results, using a mixed-methods design, showed that these students significantly improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…More specifically, this study was carried out in a school located in a region where socioeconomic developmental level was below the average. One of the few studies on PBL for disadvantaged students showed that multimedia‐enriched problem‐based learning environment enhanced these students' attitudes toward science 9 . The researchers also found that there was a positive association between science knowledge and attitude toward science.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…More specifically, this study was carried out in a school located in a region where socioeconomic developmental level was below the average. One of the few studies on PBL for disadvantaged students showed that multimedia‐enriched problem‐based learning environment enhanced these students' attitudes toward science 9 . The researchers also found that there was a positive association between science knowledge and attitude toward science.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, when the goals of science education are examined, it is seen, that not only improvements in students' outcomes in cognitive domain but also in affective domain are emphasized 8 . Among the outcomes in affective domain, attitude emerges as an important factor in students' motivation and performance 9 . In addition, students' attitudes are argued to have great influence on their future career choices 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inquiry-based learning is more effective than non-inquiry-based learning methods in academic achievement in science and mathematics courses (Kogan & Laursen, 2014;Wilson, Taylor, Kowalski, & Carlson, 2010). The effects of the inquiry method on learning may be increased with technology support (Lee, Linn, Varma, & Liu, 2010;Liu, Liu, Pan, Zou, & Li, 2019;Merritt, Lee, Rillero, & Kinach, 2017).…”
Section: Review Of Studies Investigating Effects Of Online Teaching Mmentioning
confidence: 99%
“…Though the learning process will be better if it is support by the use of adequate media. Learners will interact directly with learning resources with the help of media that can lead to the achievement of the learning goals [5].…”
Section: Introductionmentioning
confidence: 99%